Pengaruh Penambahan Tepung Wortel (Daucus carota L.) dengan Konsentrasi yang Berbeda dalam Pakan Komersial terhadap Intensitas Warna Ikan Cupang Halfmoon (Betta splendens) - Al Arif Sofriyadi; Sarmin; Denny Indra Yudistira; Aryanti Indah Setyastuti; RR. Nurina Ayu; Any Kurniawati; Mardiyana (Cenderawasih University, 2023)
Ornamental fish is a type of fish that lives in fresh water or in the sea that has a beautiful and attractive body shape or color. One type of freshwater ornamental fish that has a unique difference from the others is Betta ornamental fish. Betta fish is one type of ornamental fish that is in demand by the public, but the breeders of this betta fish are mostly confused about how to increase the brightness of the color of betta fish. Based on this background, this study aims to determine the effect of adding carrot flour with different concentrations in commercial feed on the color intensity of halfmoon betta fish (Betta splendens).This study used an experimental method with a Complete Randomized Design (RAL) of 4 treatments and 3 repeats. Then the variables observed include, fish brightness, fish weight, fish length, fish daily length, fish survival, and water quality. Furthermore, the observed data and data processing is carried out with SPSS statistical software 25.The addition of carrot flour in commercial feed can affect markedly (P>0.05). The addition of P4 treatment carrot flour at a dose of 95% pellets and 15% carrot flour in commercial feed, gave good results on the brightness of the color of Betta fish with an average value of 5.0 compared to other treatments that were given the addition of less carrot flour.